IMPLEMENTASI PENGGUNAAN APLIKASI MICROSOFT POWER BI DALAM MELIHAT STATISTIK HUTANG NEGARA DI DUNIA - Julfia, Fenty Tristanti; Satryawati, Eka; Ariani, Wiga; Ramadhan, Muhammad Rizqi (Universitas Ivet, 2024)
In the era of globalization, an in-depth understanding of sovereign debt statistics is crucial to ensure economic stability. One solution that can significantly contribute to the analysis of sovereign debt data is the application of Business Intelligence (BI) technology, such as Microsoft Power BI. The importance of in-depth understanding of sovereign debt statistics is crucial, considering that sovereign debt can affect economic policy, currency stability, and various other aspects. Therefore, an efficient approach is needed to manage and analyze data related to sovereign debt in a holistic manner. One of the solutions that can make a significant contribution to the analysis of data on data analysis is the application of Business Intelligence (BI) technology, such as Microsoft Power BI. Power BI enables effective data visualization that can be accessed by various stakeholders, making it easier to understand trends, patterns, and the impact of sovereign debt. This research will focus on the application of Power BI to analyze sovereign debt statistics in various parts of the world, with the aim of contributing positively to the understanding and management of sovereign debt globally through the perspective of advanced information technology